How do ferry operators communicate their engagement with sustainability issues? Comparison of the Baltic and the Adriatic ferry operators - Natalia Wagner; Ewa Hącia; Aleksandra Łapko; Roma Strulak-Wójcikiewicz; Gorana Jelić Mrčelić; Eli Marušić (PLoS ONE, 2026)
A successful transition toward sustainable shipping requires continuous measurement of progress and transparent communication of results. The aim of this paper is to evaluate and compare the attitude to sustainability reporting applied by ferry operators in the Baltic and the Adriatic Seas in the context of sustainability issues relevant to the ferry shipping market. The research framework combines two phases of empirical research – (1) expert evaluation and (2) website content analysis to assess whether ferry operators share information about their engagement in corporate sustainability in relation to the examined sustainability categories. It is found that the operators functioning in the Baltic area showed much greater engagement in informing about sustainability issues compared to those operating in the Adriatic area, even though in both areas the predominant level of engagement was very low. Moreover, the Baltic operators usually concerned different activities than those communicated by the Adriatic operators.